Informational continuity of medication management in transitions of care: qualitative interviews with stakeholders from the HYPERION-TransCare study - Dinh, Truc Sophia; Hanf, Maria; Klein, Astrid-Alexandra; Brueckle, Maria-Sophie; Rietschel, Lisa; Petermann, Jenny; Brosse, Franziska; Schulz-Rothe, Sylvia; Klasing, Sophia; Muth, Christiane; Seidling, Hanna; Engler, Jennifer; et al. (PLOS ONE, 2024)
Background The transition of patients between inpatient and outpatient care can lead to adverse events and medication-related problems due to medication and communication errors, such as medication discontinuation, the frequency of (re-)hospitalizations, and increased morbidity and mortality. Older patients with multimorbidity and polypharmacy are particularly at high risk during transitions of care. Previous research highlighted the need for interventions to improve transitions of care in order to support information continuity, coordination, and communication. The HYPERION-TransCare project aims to improve the continuity of medication management for older patients during transitions of care. Methods and findings Using a qualitative design, 32 expert interviews were conducted to explore the perspectives of key stakeholders, which included healthcare professionals, patients and one informal caregiver, on transitions of care. Interviews were conducted between October 2020 and January 2021, transcribed verbatim and analyzed using content analysis. We narratively summarized four main topics (stakeholders’ tasks, challenges, ideas for solutions and best practice examples, and patient-related factors) and mapped them in a patient journey map. Lacking or incomplete information on patients’ medication and health conditions, inappropriate communication and collaboration between healthcare providers within and across settings, and insufficient digital support limit the continuity of medication management. Conclusions The study confirms that medication management during transitions of care is a complex process that can be compromised by a variety of factors. Legal requirements and standardized processes are urgently needed to ensure adequate exchange of information and organization of medication management before, during and after hospital admissions. Despite the numerous barriers identified, the findings indicate that involved healthcare professionals from both the inpatient and outpatient care settings have a common understanding.
Online veröffentlicht: 4. April 2024
Gesehen am 28.01.2025